2019
DOI: 10.1002/tea.21607
|View full text |Cite
|
Sign up to set email alerts
|

Positioning participation in the NGSS era: What counts as success?

Abstract: The Next Generation Science Standards (NGSS) strives to shift science learning from the teacher as a single cognitive agent, to a classroom community in which participants are working together in directing the classroom's communal knowledge to figure out questions about how phenomena occur, and building, testing, and refining their ideas to address those questions. To achieve this type of classroom environment, teachers should attend to students' knowledge and ideas and pay attention to how students are locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, some work has shown that the storyline approach can have positive effects on class participation across gender, racial, and ethnic groups (Krumm et al, 2020). In addition, whole class discussions in storyline units have been shown to position students as legitimate participants who work together to understand scientific phenomena (Zangori & Pinnow, 2020). Nevertheless, in that same study Zangori and Pinnow also found that not every discussion achieved these positive outcomes, highlighting again the need to understand how we can support teachers who use these materials to consistently engage students in discussions that support collective sensemaking.…”
Section: Storyline Curriculamentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, some work has shown that the storyline approach can have positive effects on class participation across gender, racial, and ethnic groups (Krumm et al, 2020). In addition, whole class discussions in storyline units have been shown to position students as legitimate participants who work together to understand scientific phenomena (Zangori & Pinnow, 2020). Nevertheless, in that same study Zangori and Pinnow also found that not every discussion achieved these positive outcomes, highlighting again the need to understand how we can support teachers who use these materials to consistently engage students in discussions that support collective sensemaking.…”
Section: Storyline Curriculamentioning
confidence: 97%
“…One of the key ways to support this collective sensemaking is through classroom discourse that encourages students to figure out ideas based on evidence collected in class (Lemke, 1990;Zangori & Pinnow, 2020). Classroom talk is well-researched and much is known about how to support students in engaging in the discourse of science (Park et al, 2017).…”
mentioning
confidence: 99%
“…The teacher's discursive roles are important because the ways in which the teacher communicates with students can expand or shut down students' sense‐making practices (Schwarz et al, 2020). This teacher role is more crucial in the elementary science classroom since the elementary classroom is an important time for children to start building their relationship with science (Zangori & Pinnow, 2020). Nevertheless, there are only a few studies that have examined teacher discourse in terms of epistemological messages in modeling‐based elementary science classrooms.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Achieving this change entails a series of shifts over an extended period of purposeful and reflective activity (see Windschitl et al, 2008). The shifts involve abandoning traditional approaches that emphasize right answers, memorized procedures, and the role of the teacher as the possessor of knowledge, to students participating as agents in knowledge construction (Miller et al, 2018;Zangori & Pinnow, 2020). Teachers must create environments of productive uncertainty (Allen & Heredia, 2020), where students use scientific practices to figure out how phenomena work and build their understanding over time.…”
Section: Teacher Change In Practicementioning
confidence: 99%